VIRAL HEALTH MISINFORMATION FROM GEOCITIES TO COVID-19 - Walker, Shawn; Roschke, Kristy; Padejski, Djordje; Simeone, Michael; Muldoon, Anna; Brown, Major (AoIR Selected Papers of Internet Research, 2023)
Although often discussed in the public discourse as a phenomenon newly exacerbated by social media, the use of the Internet to spread health-related misinformation is as old as the Internet itself. Techniques, networks, and narratives from prior novel health outbreaks such as HIV or Ebola continue to circulate and are repurposed in the current COVID-19 pandemic. We examine and compare two case studies of health misinformation — HIV mis/disinformation in from the mid-1990s to early 2000s circulating in GeoCities and the role of official COVID-19 Dashboards in present-day COVID-19 mis/disinformation. This contributes to our understanding of current and historical health misinformation as well as the connections between them.